Development Of A Dental Emergency Response App: Agile Solutions For Timely Patient Care - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research aims to develop a responsive and efficient emergency dental application for providing emergency dental care to patients. The research includes user needs analysis, application development, and user acceptance evaluation stages. The agile solution's development method involves beta testing with potential users and iterative improvements based on feedback. The evaluation results indicate 87 percent of users stated that the application met their expectations. This application features essential functionalities such as integration with medical information systems, emergency notifications, interactive communication, and doctor schedule management. In conclusion, this application is expected to enhance responsiveness, efficiency, and quality of emergency dental care services, providing timely and quality solutions in handling dental emergency cases.